Staregi Perancangan Penilaian Kinerja berbasis Kompetensi Departemen SOP di PT. HJ BUSANA INDAH - Terra Cipta Alfarrizy; Anton Budi Santoso (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The global garment manufacturing industry faces increasing demands for product quality, technical audit compliance, and consistent implementation of operational procedures. PT. HJ Busana Indah, as a garment manufacturing company serving international buyers, underwent several technical audits throughout 2025 covering aspects of 5S, Product Safety, Mold Preventive, Maintenance, and SOP Operation. Although the overall audit results indicated relatively good performance, a significant decline was identified in the Athleta technical audit conducted in December 2025, where the audit score dropped to zero due to a critical finding related to Product Safety. This condition poses a serious risk to buyer confidence and may potentially affect future order allocation. These findings indicate fundamental issues in operational control, particularly related to the competency of the Standard Operating Procedure (SOP) Department, as Product Safety constitutes a core responsibility of this department. However, the existing performance appraisal system remains generic and administrative, limiting its ability to measure job-specific competencies effectively. Therefore, this study aims to design a competency-based performance appraisal system aligned with the work process characteristics of the SOP Department at PT. HJ Busana Indah. This research adopts a qualitative descriptive-exploratory approach through interviews, observations, and document analysis. The study results in a proposed competency-based performance appraisal system expected to support audit readiness and sustainable competency development within the SOP Department.